2020
DOI: 10.1167/jov.20.6.14
|View full text |Cite
|
Sign up to set email alerts
|

Faces under continuous flash suppression capture attention faster than objects, but without a face-evoked steady-state visual potential: Is curvilinearity responsible for the behavioral effect?

Abstract: Face perception is a vital part of human social interactions. The social value of faces makes their efficient detection evolutionarily advantageous. It has been suggested that this might occur nonconsciously, but experimental results are equivocal thus far. Here, we probe nonconscious face perception using a novel combination of binocular rivalry with continuous flash suppression and steady-state visually evoked potentials. In the first two experiments, participants viewed either non-face objects, neutral face… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(96 reference statements)
1
3
0
Order By: Relevance
“…The average waveform across trials and participants revealed a sinusoidal pattern of activity, where neural amplitude peaked first at approximately 0.75 s (positive peak over parietal-occipital electrodes, negative peak over frontal-central electrodes) and then again with opposite polarity at approximately 2.25 s (Figure 3A). Due to there being no sudden stimulus onset, typical face-related ERP components such as a P100 and N170 were absent from neural activity, similar to previous studies using conscious suppression techniques (Sterzer et al, 2009;Kaunitz et al, 2011;Yokoyama et al, 2013;Schlossmacher et al, 2017;Engell and Quillian, 2020;Poland et al, 2021) and studies where visual stimuli gradually increase in contrast (O'Connell et al, 2012).…”
Section: Central-parietal Positivity Componentsupporting
confidence: 85%
“…The average waveform across trials and participants revealed a sinusoidal pattern of activity, where neural amplitude peaked first at approximately 0.75 s (positive peak over parietal-occipital electrodes, negative peak over frontal-central electrodes) and then again with opposite polarity at approximately 2.25 s (Figure 3A). Due to there being no sudden stimulus onset, typical face-related ERP components such as a P100 and N170 were absent from neural activity, similar to previous studies using conscious suppression techniques (Sterzer et al, 2009;Kaunitz et al, 2011;Yokoyama et al, 2013;Schlossmacher et al, 2017;Engell and Quillian, 2020;Poland et al, 2021) and studies where visual stimuli gradually increase in contrast (O'Connell et al, 2012).…”
Section: Central-parietal Positivity Componentsupporting
confidence: 85%
“…Red-blue anaglyph glasses were used to allow the presentation of different information to each eye (Engell & Quilliam, 2020;Gomes, Soares, Silva, & Silva, 2018;Korb, Osimo, Suran, Goldstein, & Rumiati, 2017;Zhou et al, 2020). In the present study, the red filter lens was used over the left eye and the blue filter lens over the right eye.…”
Section: Displaymentioning
confidence: 99%
“…To the best of our knowledge, these selection criteria have not used in combination on previous studies, and due to the stringent nature of these criteria, we ended discarding an important number of participants (12 out 29 or 41%). While this is not unique to our study (see for example [34]) we understand the need to replicate our results to assess their full impact. As noted before, however, priming on the discarded participants was not significantly different from priming on the included participants (Fig 3), indicating that our results cannot be explained by our selection criteria.…”
Section: Discussionmentioning
confidence: 94%